1994
DOI: 10.1901/jeab.1994.62-109
|View full text |Cite
|
Sign up to set email alerts
|

Within‐session Changes in Responding During Several Simple Schedules

Abstract: Pigeons' key pecking was reinforced by food delivered by several fixed-interval, variable-ratio, and differential-reinforcement-of-low-rate schedules. Rate of responding, number of responses per reinforcer, length of postreinforcement pause, running response rate, and the time required to collect an available reinforcer changed systematically within sessions when the schedules provided high rates of reinforcement, but usually not when they provided low rates. These results suggest that the factors that produce… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
46
0
1

Year Published

1996
1996
2014
2014

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 53 publications
(49 citation statements)
references
References 21 publications
2
46
0
1
Order By: Relevance
“…On the contrary, many other factors might contribute. To date, our research has questioned several alternative explanations, including recovery from handling (McSweeney & Johnson, 1994), anticipation of events that follow the session (e.g., feeding or handling; , changes in a general motivational state (e.g., arousal; McSweeney, , changes in interference from adjunctive behaviors or exploration (Roll & McSweeney, 1997), changes in factors produced by the act of responding (e.g., muscular warm-up, fatigue; McSweeney, McSweeney, Weatherly, Roll, & Swindell, 1995;Melville, Rybiski, & Kamrani, 1996;, and changes in "attention" to the task, defined in several ways (McSweeney, Roll, & Weatherly, 1994;McSweeney, Weatherly, & Swindell, 1996c;Melville & Weatherly, 1996). An opponent-process explanation (e.g., Solomon & Corbit, 1974) also seems unlikely because early-session increases in responding sometimes occur without late-session decreases and vice versa.…”
Section: Changes In Reinforcer Effectiveness Produce Within-session Cmentioning
confidence: 99%
See 1 more Smart Citation
“…On the contrary, many other factors might contribute. To date, our research has questioned several alternative explanations, including recovery from handling (McSweeney & Johnson, 1994), anticipation of events that follow the session (e.g., feeding or handling; , changes in a general motivational state (e.g., arousal; McSweeney, , changes in interference from adjunctive behaviors or exploration (Roll & McSweeney, 1997), changes in factors produced by the act of responding (e.g., muscular warm-up, fatigue; McSweeney, McSweeney, Weatherly, Roll, & Swindell, 1995;Melville, Rybiski, & Kamrani, 1996;, and changes in "attention" to the task, defined in several ways (McSweeney, Roll, & Weatherly, 1994;McSweeney, Weatherly, & Swindell, 1996c;Melville & Weatherly, 1996). An opponent-process explanation (e.g., Solomon & Corbit, 1974) also seems unlikely because early-session increases in responding sometimes occur without late-session decreases and vice versa.…”
Section: Changes In Reinforcer Effectiveness Produce Within-session Cmentioning
confidence: 99%
“…For example, altering characteristics of the reinforcers such as their rate of delivery (McSweeney, 1992;McSweeney, Roll, & Cannon, 1994;McSweeney, Roll, & Weatherly, 1994;McSweeney & Swindell, 1999a; . At this time, changes in the effectiveness of the reinforcer appear to be the major, but not the sole, determinant of within-session changes in responding.…”
Section: Changes In Reinforcer Effectiveness Produce Within-session Cmentioning
confidence: 99%
“…Within-session changes in response rates imply that absolute response rates will differ, depending on the time in the session at which responding is measured and on the length ofthe session over which responding is averaged. Because significant within-session changes in responding have been reported for a wide variety of schedules, including simple (e.g., McSweeney, Roll, & Weatherly, 1994), multiple (e.g., McSweeney, 1992), and concurrent (e.g., McSweeney et aI., 1995), within-session changes create problems for interpreting absolute response rates during a wide variety of procedures.…”
Section: Discussionmentioning
confidence: 99%
“…In their study, PRPs increased within a session on FI and differential-reinforcementof-low-rate schedules while local response rates showed the opposite pattern. McSweeney et al (1994) noted that previous studies of PRPs on FI schedules showed either no change (Palya, 1992) or increases (Collier, 1962) in pauses.…”
mentioning
confidence: 96%
“…According to this theory, these processes alter the effectiveness of reinforcers within a session, and if this is the case, PRPs may also change. Unfortunately, with the exception of McSweeney, Roll, and Weatherly (1994), little attention has been paid to within-session changes in PRPs. In their study, PRPs increased within a session on FI and differential-reinforcementof-low-rate schedules while local response rates showed the opposite pattern.…”
mentioning
confidence: 99%